Analysis of Risk Factors Associated with Stroke in Young Adults: A Prospective Study - Hossain, MZ; Ahmed, SU; Sarder, MH; Dasgupta, R; Das, A; Sarker, RN; Azad, KAK; Arif, SM; Mohammad, QD (Journal of Dhaka Medical College, 2010)
Objective: Stroke in young patients is not common. The purpose of this study was to find out the risk factors of stroke in young adults in Bangladesh and to compare with different other studies. Methods: 85 young adult cases of stroke patients with the age ranging from 14 to 45 years, admitted in different medical units of Dhaka Medical College Hospital from January 2008 to July 2009, were studied. The risk factors for stroke and the distribution of stroke types were analyzed. Results: The specific age group (14-45 years old) included 6% of patients of all ages admitted for stroke. Among 85 patients, cerebral infarction was diagnosed in 52 patients (61%). Intracerebral hemorrhage (without trauma) was diagnosed in 25 patients (29.4%). Subarachnoid hemorrhage was found in 7 young patients (8.24%). The most common risk factors for ischemic stroke were hypertension (57.68%), hypercholesterolemia (38.46%), diabetes (34.61%), smoking (32.69%), premature atherosclerosis (11.54%). Regarding aetiology of cerebral infarction, the majority due to cardiogenic emboli (75%). The use of oral contraceptives, pregnancy, SLE, migraine and moya moya disease were infrequent causes of cerebral infarction. In ischemic stroke, the ratio of cardiogenic emboli & other factors were 3:1. The most common risk factors for hemorrhagic stroke were hypertension (63.63%), hypercholesterolemia (39.39%), diabetes (36.54%) & smoking (33.33%). Conclusion: Hypertension, Diabetes, tobacco smoking, premature atherosclerosis & rheumatic valvular heart disease are growing problems in the developing countries. According to our finding, identification & treatment of hypertension, dyslipidaemia, diabetes & rheumatic valvular heart disease & cessation of smoking are proper measures to prevent morbidity & mortality. Key words: Risk factors; stroke; young adult. DOI: 10.3329/jdmc.v18i2.6265 J Dhaka Med Coll. 2009; 18(2) : 95-99